Immunosuppression in patients with grade 3 acute‐on‐chronic liver failure at transplantation: A practice analysis study. Issue 4 (15th January 2022) - Faitot, Francois; Artzner, Thierry; Michard, Baptiste; Besch, Camille; Schenck, Maleka; Herbrecht, Jean‐Etienne; Janssen Langenstein, Ralf; Maestraggi, Quentin; Guillot, Max; Harlay, Marie‐Line; Castelain, Vincent; Addeo, Pietro; et al.
Abstract: Transplantation for patients with acute‐on‐chronic liver failure grade 3 (ACLF3) has encouraging results with 1‐year‐survival of 80‐90%. These patients with multiple organ failure meet the conditions for serious alterations of drug metabolism and increased toxicity. The goal of this study was to identify immunosuppression‐dependent factors that affect survival. This retrospective monocentric study was conducted in patients with ACLF3 consecutively transplanted between 2007 and 2019. The primary endpoint was 1‐year survival. Secondary endpoints were overall survival, treated rejection, and surgical complications. Immunosuppression was evaluated as to type of immunosuppression, post‐transplant introduction timing, trough levels, and trough level intra‐patient variability (IPV). One hundred patients were included. Tacrolimus IPV < 40% ( P  = .019), absence of early tacrolimus overdose ( P  = .033), use of anti‐IL2‐receptor antibodies ( P  = .034), and early mycophenolic acid introduction ( P  = .038) predicted 1‐year survival. Treated rejection was an independent predictor of survival ( P  = .001; HR 4.2 (CI 95%: 1.13‐15.6)). Early everolimus introduction was neither associated with higher rejection rates nor with more surgical complications. Management of immunosuppression in ACLF3 critically ill patients undergoing liver transplantation is challenging. Occurrence and treatment of rejection impacts on survival. Early introduction of mTOR inhibitor seems safe and efficient in this situation.